2012
DOI: 10.1111/j.1399-3062.2012.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B prophylaxis post liver transplantation with newer nucleos(t)ide analogues after hepatitis B immunoglobulin discontinuation

Abstract: Newer nucleos(t)ide analogues (NUCs) have better resistance profiles making hepatitis B immunoglobulin (HBIG)-sparing protocol an attractive prophylactic approach against hepatitis B virus (HBV) recurrence after liver transplantation (LT). We evaluated the risk of HBV recurrence after withdrawal of HBIG in patients who had been under HBIG plus NUCs after LT. Stable patients without HBV recurrence after LT while receiving combination of HBIG plus NUCs for at least 12 months were eligible for HBIG discontinuatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 23 publications
8
62
0
Order By: Relevance
“…Six studies were from USA (8,10,12,18,19,21), three from China (7,14,20), two from Spain (13,16), two from Japan (9,25) and one study from Netherlands (17), India (23), Taiwan (22) and Greece (11). Eleven studies evaluated the combination of HBIG with hgbNA(s) (7,9,10,(12)(13)(14)16,18,19,22,25), while eight studies (8,11,(17)(18)(19)(20)(21)23) evaluated patients under hgbNA(s) after HBIG discontinuation or without any HBIG (Figure 1). There was only one randomized controlled trial (10), while seven were prospective cohort (7,11,12,17,18,21,23) and nine retrospective cohort studies (8,9,13,14,16,19,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies were from USA (8,10,12,18,19,21), three from China (7,14,20), two from Spain (13,16), two from Japan (9,25) and one study from Netherlands (17), India (23), Taiwan (22) and Greece (11). Eleven studies evaluated the combination of HBIG with hgbNA(s) (7,9,10,(12)(13)(14)16,18,19,22,25), while eight studies (8,11,(17)(18)(19)(20)(21)23) evaluated patients under hgbNA(s) after HBIG discontinuation or without any HBIG (Figure 1). There was only one randomized controlled trial (10), while seven were prospective cohort (7,11,12,17,18,21,23) and nine retrospective cohort studies (8,9,13,14,16,19,…”
Section: Resultsmentioning
confidence: 99%
“…In total, 94 articles were initially identified from the literature search, but only 20 studies (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) fulfilled the inclusion criteria ( Figure A1). Of two studies (14,15) from one center in China with overlapping study periods, only the latest one (14) was included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that with appropriate patient selection (high-vs. low-risk), recurrence could be minimized (26,29). The factors that impact recurrence include the presence of hepatocellular carcinoma (HCC) are LT, HCC recurrence, and types of HCC treatment (13).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Cholongitas et al (13) found no significant differences in renal function (evaluated by GFRs using Cr-EDTA) between the group of patients under nucleotide analogues (i.e., adefovir or TDF [with or without LAM]) compared with under nucleoside analogues (i.e., entecavir monoprophylaxis) during the followup period.…”
Section: Discussionmentioning
confidence: 99%